A Vaginal Inlay for Reduction of Stress Urinary Incontinence: Outcome of a Randomized Clinical Trial and Four User Acceptance Studies. (15th February 2021) - Jonasson, Aino Fianu; Bryder, Karin; Sthengel, Elisabeth
Abstract : A multicenter, randomized, controlled clinical trial and four postmarket user acceptance investigations were carried out to document the safety, performance, and user acceptance of Efemia Bladder Support, a novel vaginal inlay for the temporary reduction of stress urinary incontinence (SUI). The clinical investigation enrolled 97 women diagnosed with SUI, randomized 3 : 1 to either treatment or standard care (control). The primary endpoint was reduction of urine leakage, measured as change in pad weight baseline week compared with treatment week. Secondary endpoints were treatment success, calculated as the percentage of subjects with >70% reduction in pad weight, reduction in incontinence episodes, and quality of life (QoL). 75 women (77%) completed the clinical investigation. No serious adverse events occurred. The treatment group reached a 55% (p < 0.001 ) mean reduction of total leakage compared to the control arm. A subanalysis, involving only leakage during provocation testing (coughing and jumping), showed a 67% (p < 0.001 ) mean reduction of leakage. No significant effect on QoL could be observed. 51% of the women answered "yes" to the question if they would use the device to reduce SUI. The user acceptance of the device was further investigated in four postmarket studies, using an improved device design with a slimmer centerpiece and a thinner handle, while keeping the effect achieving parts of the device unchanged. An average of 74% of the 102 participants in the postmarket studies reported that they were likely to continue using Efemia. The highest user satisfaction was seen in the two studies evaluating the use of Efemia during exercise, where 83% and 88% of the women were likely to continue using Efemia. It can be concluded that Efemia is a safe, well-tolerated, and effective alternative for reducing SUI, both in everyday life and during physical exercise.